Prediksi Pola Kecelakaan Lalu Lintas Menggunakan Metode Analisa Asosiatif - Ahmad Soderi (Fakultas Teknik Universitas Persada Indonesia YAI, 2019)
The data of traffic accident can be processed into information that is important for Police Department. Those important information researched is to analyze the traffic accident data to find out is there any link between the occurrence of an accident to a certain brand of vehicle. This research implementing data mining method to process the data traffic accident by using data mining for prediction techniques called Apriori Method. Apriori Method is used to identify a pattern of accidents based on brand, type of vehicles, and the vehicle’s color. The results are used to estimate whether there is any correlation between the occurrences of a traffic accident to a particular brand. The result can help the Police Department to find out whether there is any correlation between the occurrence of traffic accidents to the brand, type and the color of vehicle. Keyword: Rule Based Classification, Apriori, Brand Loyalty, Traffic Accident